USE OF SIBELIUS SOFTWARE ON UNDERSTANDING OF KNOWLEDGE MATERIAL LEARNING THEORY OF SMK VOCATIONAL SCHOOL - Williantoro, Guntur (EDUTECH, 2020)
This study aims to examine (1) the scientific implementation using the Sibelius software media (2) the effect of using Sibelius Software on the understanding and ability of music theory knowledge (3) the influence on the understanding and ability of music theory knowledge by not using the Sibelius software. This research is an experimental research with Pretest-Posttest design, Nonequivalent Control Group Design. This study used an experimental class and a control class. The population of the study was students of music class I and class II music class I at SMKN 12 Surabaya. The experimental results showed that the pretests of the control class and experimental class students tended to be almost the same. The posttest learning result data showed the difference in the average score between the experimental class and the control class was categorized as very high. Based on the results of the average score, it was obtained that there was an increase in understanding of the material knowledge of music theory subjects in class X SMK in the first semester. Penelitian ini bertujuan untuk menguji (1) Implementasi saintifik menggunakan media software sibelius  (2) pengaruh penggunaan Software Sibelius terhadap pemahaman dan kemampuan pengetahuan teori musik (3) pengaruh terhadap pemahaman dan kemampuan pengetahuan teori musik dengan tidak menggunakan  software sibelius. Penelitian ini merupakan penelitian eksperimen dengan desain Pretest-Posttest, Nonequivalent Control Group Design. Penelitian ini menggunakan kelas eksperimen dan kelas kontrol. Populasi penelitian adalah siswa kelas musik I  dan kelas musik II semester I di SMKN 12 Surabaya. Hasil eksperimen menunjukkan pretest mahasiswa kelas kontrol dan kelas eksperimen cenderung hampir sama. Data hasil belajar posttest menunjukkan selisih skor rata-rata antara kelas eksperimen dan kelas kontrol berkategori sangat tinggi. Berdasarkan hasil nilai rata-rata diperoleh bahwa terjadi peningkatan pemahaman materi pengetahuan mata pelajaran Teori musik SMK kelas X semester I.